Merti Desa Tradition As The Local Wisdom of The Java Community in Indonesia - Kundharu Saddhono; Raheni Suhita; Titi Setyoningsih (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Suruhan Hamlet, Rogomulyo Village is an area in Central Java, precisely in Kaliwungu District, Semarang Regency. People in this region continue to preserve traditions, one of which is the Merti Desa tradition. This research was conducted to determine (1) the meaning of the Merti Desa tradition (uborampe, art performance) for the residents of Suruhan Hamlet, Rogomulyo Village; (2) the differences between the Merti Desa and the other traditions intended to pray for the ancestors in the same area, and their comparison with other regions; (3) the community's efforts in maintaining the Merti Desa tradition. This study employed a qualitative method involving a phenomenology approach. It focused on community activities in carrying out a tradition. The data were collected through journals, news articles, field observations, and interviews. The findings indicated that the people of Suruhan Hamlet, Rogomulyo Village preserved the Merti Desa tradition as local wisdom aimed to express public gratitude to God Almighty. Besides, several other traditions were also being preserved, including the Nyadran, to express gratitude and pray for the ancestors. The implementation of the Merti Desa tradition contained many values or meanings in each of its stages.